Magnet hospital research pilot project conducted in hospitals in Western Australia - Naude, Marita; McCabe, Rebecca (eContent Management Pty Ltd, 2005)
The factors causing nurses to leave nursing are well known and published. The main aim of the research pilot project was to explore and describe the reasons that attract nurses to a specific hospital and that motive them to remain working at that hospital. Data were collected through surveys of different categories of nurses working in selected 'Magnet Hospitals' in Perth (Western Australia). Biographical data were analysed through quantitative methods and content analysis was employed to analyze qualitative data. Motivational findings indicate specific organizational factors (such as staff development programs) and significant personal circumstances.